1989
DOI: 10.1111/1523-1747.ep12277125
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronate Accumulation in Human Epidermis Treated with Retinoic Acid in Skin Organ Culture

Abstract: Retinoic acid (RA) has been shown to retard the differentiation of epidermal keratinocytes by several morphologic and biochemical criteria. In this study, the epidermal content and localization of hyaluronate (HA), as well as its synthesis and disappearance in human skin organ culture, were characterized to test the idea that some of the RA influences on epidermal differentiation are associated with keratinocyte HA metabolism. RA stimulated the incorporation of 3H-glucosamine into HA by up to 60% at concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
78
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 37 publications
10
78
0
Order By: Relevance
“…An inverse correlation between the content of hyaluronan in the spinous cell layer and the indicators of epidermal differentiation has also been noted with other effectors like vitamin A (38) and EGF (39), both of which stimulate hyaluronan synthesis and inhibit differentiation. Conversely, we have found that pharmacological concentrations of hydrocortisone enhance differentiation but inhibit hyaluronan synthesis (40) and Has2 expression.…”
Section: Discussionmentioning
confidence: 78%
“…An inverse correlation between the content of hyaluronan in the spinous cell layer and the indicators of epidermal differentiation has also been noted with other effectors like vitamin A (38) and EGF (39), both of which stimulate hyaluronan synthesis and inhibit differentiation. Conversely, we have found that pharmacological concentrations of hydrocortisone enhance differentiation but inhibit hyaluronan synthesis (40) and Has2 expression.…”
Section: Discussionmentioning
confidence: 78%
“…In human skin organ cultures, factors like all-trans-retinoic acid which increase hyaluronan synthesis lead to delayed differentiation [132], like in human skin in vivo. Likewise, organotypic epidermal cultures show that keratinocyte differentiation is stimulated and inhibited by factors that decrease and increase hyaluronan synthesis, respectively [133].…”
Section: Role Of the Pericellular Matrix In Mechanotransduction And Cmentioning
confidence: 99%
“…Hyaluronan is synthesized by the Has enzymes Has1, Has2, and Has3 at the plasma membrane (2). In skin epidermis, the narrow extracellular space surrounding keratinocytes contains a high concentration of hyaluronan, but it is found mainly between the basal and spinous cell layers of normal human epidermis and much less in terminally differentiated layers (3). Both in normal and diseased epidermis, keratinocyte growth and differentiation are regulated by paracrine and endocrine signaling molecules, such as EGF 1 and the nuclear hormone all-trans-RA.…”
mentioning
confidence: 99%
“…Both in normal and diseased epidermis, keratinocyte growth and differentiation are regulated by paracrine and endocrine signaling molecules, such as EGF 1 and the nuclear hormone all-trans-RA. Interestingly, hyaluronan synthesis rate is stimulated by EGF in epidermal keratinocytes in monolayer (4) and organotypic cultures (5) and by all-trans-RA in human skin organ cultures (3). Direct evidence for the biological role of hyaluronan in epidermal keratinocytes emerged by the finding that Has2-mediated hyaluronan synthesis controls the migration rate of keratinocytes in scratch-wounded monolayer cultures (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation